Penyusun Laporan Keuangan Berbasis Excel For Accouting Pada Panti Asuhan Aisyiyah Untuk Meningkatkan Efisiensi Dan Akurasi Laporan Keuangan - Anggraini, Dina; Sartika, Dewi; Rahmi, Fitria; Mulyani, Fitrah; Yanti, Nino Sri Purnama; ., Nini; Dahar, Reni; K, Yunita Valentina; Rahmi, Latifa; Putri, Tiffany Syentia; Revalinda, Gustia; Widawati, Yeni Riska; Abdilah, Tri Khahfi; Azman, Heru Aulia (LPPM Universitas Dharma Andalas, 2025)
Aisyiyah Orphanage is a non-profit social institution that plays an important role in protecting and fulfilling children’s rights. The orphanage is located in Padang City. However, in managing its financial administration, the orphanage still relies on a manual recording system, which results in challenges related to efficiency, accuracy, and transparency of financial reports provided to donors. To address these issues, the Accounting PKM Team of Universitas Dharma Andalas implemented a community service program entitled “Preparation of Excel-Based Financial Statements for Aisyiyah Orphanage to Improve the Efficiency and Accuracy of Financial Reporting.” This program aims to assist the orphanage management in digitally managing financial records using Microsoft Excel. The system is designed to record transactions and automatically generate easy-to-understand financial statements. The results of the program indicate that the implementation of the system has improved the efficiency, accuracy, and transparency of the orphanage’s financial reports. In addition, the program has enhanced the orphanage’s human resource capacity in digital financial literacy.